Methods of calculation of cross section of reaction ¹¹⁵In(γ, n) ¹¹⁴mIn - Zhaba, V.I.; Parlag, A.M. (Вопросы атомной науки и техники, 2015)
The cross section of reaction ¹¹⁵In(γ, n) ¹¹⁴mIn is expected by different methods. Results of the got cross section it is well comported inter se the Penfold-Leiss and Tikhonov's methods. The calculation of cross section is conducted the Penfold-Leiss method with smoothing out by the method of iterations. Number of iterations n = 1; 3; 5. In the programmatic package of TALYS-1.4 got cross section for five models of closeness of levels. Theoretical and experimental results well coincide in a maximum. Переріз реакції ¹¹⁵In(γ, n) ¹¹⁴mIn розраховано різними методами. Результати отриманого перерізу методами Пенфольда-Лейсса і Тіхонова добре узгоджуються між собою. Розрахунок перерізу методом Пенфольда-Лейсса проведено зі згладжуванням методом ітерацій. Число ітерацій n = 1; 3; 5. У програмному пакеті TALYS-1.4 отримано переріз для п'яти моделей густини рівнів. Теоретичні та експериментальні результати добре співпадають у максимумі. Сечение реакции ¹¹⁵In(γ, n) ¹¹⁴mIn рассчитано разными методами. Результаты полученного сечения методами Пенфольда-Лейсса и Тихонова хорошо согласуются между собой. Расчет сечения методом Пенфольда-Лейсса проведен со сглаживанием методом итераций. Число итераций n = 1; 3; 5. В программном пакете TALYS-1.4 получены сечения для пяти моделей плотности уровней. Теоретические и экспериментальные результаты хорошо совпадают в максимуме.